2015
DOI: 10.1152/ajpgi.00179.2015
|View full text |Cite
|
Sign up to set email alerts
|

Zinc dyshomeostasis during polymicrobial sepsis in mice involves zinc transporter Zip14 and can be overcome by zinc supplementation

Abstract: Integrity of the immune system is particularly dependent on the availability of zinc. Recent data suggest that zinc is involved in the development of sepsis, a life-threatening systemic inflammation with high death rates, but with limited therapeutic options. Altered cell zinc transport mechanisms could contribute to the inflammatory effects of sepsis. Zip14, a zinc importer induced by proinflammatory stimuli, could influence zinc metabolism during sepsis and serve as a target for therapy. Using cecal ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 51 publications
6
67
1
1
Order By: Relevance
“…This effect was overcome through dietary zinc supplementation, leading to reduced severity of sepsis, as shown by amelioration of cytokine expression. 22 The existing literature, in addition to our findings, lends support to the role of zinc as an immunomodulatory agent in sepsis.…”
Section: Discussionsupporting
confidence: 82%
“…This effect was overcome through dietary zinc supplementation, leading to reduced severity of sepsis, as shown by amelioration of cytokine expression. 22 The existing literature, in addition to our findings, lends support to the role of zinc as an immunomodulatory agent in sepsis.…”
Section: Discussionsupporting
confidence: 82%
“…In the original characterization of the mice, Hojyo et al (52) reported that hepatic zinc concentrations were ∼30% lower in Slc39a14 −/− mice compared with controls. Other studies, however, reported no alterations in hepatic zinc levels in Slc39a14 −/− mice under normal conditions (53)(54)(55). Here, we find that hepatic zinc concentrations are 11-15% lower in Slc39a14 −/− mice at 4-16 wk of age, but were not significantly different from controls at 52 wk of age [95.1 ± 2.2 μg/g (WT) vs. 92.2 μg/g (Slc39a14 −/− ), n = 4-5 per group].…”
Section: Discussionmentioning
confidence: 94%
“…In septic states, serum Zn levels decline markedly and recover slowly with significant variation 3,4,41,42 . In the presence of severe deprivation of dietary Zn (1 ppm diet for 3 weeks), increased mortality and attributes of deficiency-induced immunoparalysis are observed; however, Zn levels in plasma and liver were not reported 40,41 .…”
Section: Resultsmentioning
confidence: 99%
“…In response to sepsis, trauma and hemorrhagic shock, plasma Zn levels decline while Zn accumulates in metabolically and immunologically active organs such as the liver and spleen 14 . Turnover of Zn within the body is also increased, reflected in sequestration in injured tissues and increased rates of disposal in the urine and stool 59 .…”
Section: Introductionmentioning
confidence: 99%